Evaluación de la larva de mosca soldado negra (Hermetia Illucens) como alternativa para la degradación de residuos sólidos urbanos (2021)
This work is concerned about the increase in solid waste due to its massive production, which is why it has been sought to implement sustainable and environmentally friendly alternatives such as composting and the search for new microorganisms that help carry out the decomposition process of organic matter efficiently and quickly such as Hermetia Illucens. The following work focuses on the importance of the larvae of the black soldier fly (MSN) for the treatment and degradation of organic waste, for which a pilot plant is proposed in a market place called Tunjuelito, located in the city from Bogotá, where 13 tons per year are available, the cost required in the process is proposed and the technical specifications are established through a proposal to implement a larval rearing system.